Critical Synthesis Package: Patient Health Questionnaire (PHQ-9) - Linda Perkowski (Association of American Medical Colleges, 2013)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education for the Patient Health Questionnaire-9 (PHQ-9),and (2) a copy of the PHQ-9 instrument and scoring key developed by Kurt Kroenke, MD, and (3) a terms of use document. The PHQ-9 is a 9-item self-report depression screening tool developed for use in primary care health centers to aid in quickly diagnosing depression and measuring depression symptom severity. Primarily used with clinical populations, it has also had limited use in samples of medical students, residents, fellows, pharmacy students and faculty physicians. The diagnostic validity of the PHQ-9 has been demonstrated in multiple populations and the psychometrics of the instrument appear to be strong. Selection of the PHQ-9 for research or education should be considered with respect to its feasibility, short administration and scoring times, its ability monitor severity of symptoms, and both the consequences and responsibilities of identifying the mental distress of subjects. Advantages of the instrument include its short length and ease of scoring. A disadvantage is the lack of use or validation studies in health sciences education. Further research is needed to evaluate the psychometric properties in samples of health science students and practitioners.